Dynamic optimum torsion axis under soil-structure interaction effects - Terzi, Vasiliki G.; Athanatopoulou, Asimina (Engineering structures, 2023)
•Optimum torsion axis is determined under soil-structure interaction effects and dynamic loading conditions.•Mathematical formulae are provided for the corresponding coordinates determination.•The proposed procedure can be implemented in any programming language.•Soil-structure interaction effects are taken into account by frequency-dependent impedance functions.•Numerical results are presented for asymmetric buildings. The present paper deals with the dynamic optimum torsion axis of asymmetric buildings under soil-structure interaction effects. The soil-foundation-building system is subject to a torsional base acceleration. Under the aforementioned loading, the optimum torsion axis is defined as the vertical axis where the sum of the squares of the resultant translation displacements receives a minimum value. The equations of motion are written and are transferred to the frequency domain in order to take into account the frequency-dependency of the foundation’s impedance functions. The optimum torsion axis criterion is applied and is further elaborated so as mathematical formulae are provided for the determination of the dynamic optimum torsion axis under soil-structure interaction effects. Numerical examples are provided by the implementation of a programming code written for this purpose. Apart from the structural eccentricity reduction another important finding is that the dynamic optimum torsion axis of a flexibly based building generally coincides with the static optimum torsion axis. A few deviations are observed in the very high frequency range.